Russian Cross-disciplinary Consensus on the diagnosis and treatment of spondyloarthritis associated with inflammatory bowel diseases - Galina V. Lukina; Oleg V. Knyazev; Elena A. Belousova; Diana I. Abdulganieva; Elena N. Aleksandrova; Igor G. Bakulin; Olga I. Barysheva; Maria А. Borisova; Bella А. Vykova; Alla А. Godzenko; Irina V. Gubonina; Tatiana V. Dubinina; et al. (Терапевтический архив)
The Russian Cross-disciplinary Consensus on the diagnositic and treatment of spondyloarthritis (SpA) in inflammatory bowel diseases (IBD) was prepared on the initiative of the Loginov Moscow Clinical Scientific Center, using the Delphic system. Its purpose was to consolidate the opinions of experts on the most actual issues of diagnosis and treatment of concomitant immuno-inflammatory diseases (SpA and IBD). An interdisciplinary approach is provided by the participation of leading gastroenterologists and rheumatologists. The working group analyzed domestic and foreign publications on the problem of curation of patients with SpA and IBD. There have been 17 statements and 2 treatment algorithms formulated. Statements 1–3 reflect the fundamental principles of management of patients with SpA and IBD. The principles of early diagnosis of SpA and IBD, including the diagnosis of complications of therapy, are described below. Eleven statements are devoted to current methods of treatment, on the basis of which 2 treatment algorithms have been developed. The statements of the Consensus were submitted to the Expert Council for consideration, edits were made, after which an online vote took place. This paper presents current recommendations for the management, diagnosis and treatment of patients with SpA and IBD.